2013
DOI: 10.5093/ejpalc2013a1
|View full text |Cite
|
Sign up to set email alerts
|

Are patients with chronic pain and fibromyalgia correctly classified by MMPI-2 validity scales and indexes?

Abstract: A study was designed to find out whether MMPI-2 validity scales and indexes differentiate between truefibromyalgia sufferers, patients with chronic organic pain and normal people, as well as whether they arecorrectly classified. 105 subjects participated in the study, 27 diagnosed with fibromyalgia and 44 withchronic organic pain and 34 were healthy people, who answered the MMPI-2 following standardinstructions. The results showed that fibromyalgia patients scored higher than the control group in the F,Fb, F-K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Amado et al (2015) have shown the utility of three statistics for forensic practice: U1, Binomial Effect Size Display (BESD), and Probability Superiority (PS). Thus, these were computed to derive the measures on the effectiveness of the scales and indexes for detecting defensiveness over the natural tendency for defensiveness i.e., responding defensively even with nothing to hide or to give a positive presentation (Osuna et al, 2015, Palmer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Amado et al (2015) have shown the utility of three statistics for forensic practice: U1, Binomial Effect Size Display (BESD), and Probability Superiority (PS). Thus, these were computed to derive the measures on the effectiveness of the scales and indexes for detecting defensiveness over the natural tendency for defensiveness i.e., responding defensively even with nothing to hide or to give a positive presentation (Osuna et al, 2015, Palmer et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Participants were informed of the objective of the study, the importance in collaborating with honest responses was underscored, and they were assured their data would remain anonymous and confidential. Finally, participants were debriefed and interviewed to ascertain the degree of motivation and implication in the task through the recall and comprehension of instructions, and by ensuring participants had understood and performed the task correctly ( Palmer et al, 2013 , Rogers, 2008 ). The results confirmed the correct execution: concordance with the clinical diagnosis registered in medical records, there were no cases of unwillingness to cooperate with the evaluation, outliers , or patterns of completely random or extremely acquiescent responses.…”
Section: Methodsmentioning
confidence: 99%
“…Por ello, se recomienda la combinación de ambos tipos de análisis (American Psychiatric Association, 2014;Arce, Fariña, Carballal, y Novo, 2006;Palmer, Borrás, Pérez-Pareja, Sesé, y Vilariño, 2013).…”
Section: Análisis De Datosunclassified